The effects of the menstrual cycle on the physiological responses to exercise in eumenorrheic women at high-altitude - Guia Tagliapietra; Tom Citherlet; Antoine Raberin; Giorgio Manferdelli; Bastien Krumm; Benjamin J. Narang; Nicolas Bourdillon; Tadej Debevec; Guido Giardini; Grégoire Millet (Bern Open Publishing, 2024)
Introduction The acute mountain sickness (AMS) prevalence increases with altitude; i.e.,10-25% at 2,500 m and 50-85% at ~5,000 m (Bärtsch & Swenson, 2013). Women are more likely affected by AMS than men (Richalet et al., 2012). AMS can affect exercise performance. However, the effects of the menstrual cycle (MC) on physiological responses to exercise and on tolerance to high-altitude (HA) remain underexplored. It has been reported that ovarian hormones stimulate ventilation in normoxic conditions (Saaresranta & Polo, 2002). Early findings suggest that running economy is lower in the mid-luteal (ML) compared to the early-follicular (EF) phase in normoxia (Goldsmith & Glaister, 2020). However, cycling efficiency at HA has not been explored yet. Thus, we investigated the effects of acute HA exposure on ventilatory responses at rest and during exercise in healthy females during two different phases of their MC. Methods Sixteen eumenorrheic women (age: 33 ± 7 yr; MC length: 27 ± 2 days; not taking any hormonal contraceptive) took part in this study. First, over a 6-month period, the participants' MC were monitored using a calendar method. Then, they reached the Torino Hut (3,375 m) by cable car and spent one night at HA on two different MC phases; i.e., during the early-follicular (EF; MC day 4 ± 1) and the mid-luteal (ML; day 20 ± 2) phases. Each time, they underwent a submaximal (1.2 W/kg) test on a cycle ergometer ~17 h after arrival at HA. In addition to this, participants filled in two questionnaires, the Lake Louise AMS Score and the Groningen Sleep Quality Scale, ~16 h after arrival at HA. Results Resting ventilation was significantly higher during EF compared to ML (15.2 ± 1.9 vs. 13.2 ± 2.5 L/min, p = 0.039), while no differences were found for ventilation during exercise (53.9 ± 13.2 vs. 53.5 ± 13.4 L/min, p = 0.695), cycling efficiency (21.7 ± 0.0% vs. 19.8 ± 0.0%, p = 0.244), saturation at rest (92.4 ± 1.3 vs. 91.3 ± 3.2%, p = 0.142) and during exercise (87.2 ± 5.7 vs. 89.0 ± 4.0%, p = 0.528). Moreover, no differences in the Lake Louise AMS (2.2 ± 1.5 vs. 1.7 ± 1.5, p = 0.266) or Groningen (8.0 ± 3.3 vs. 7.5 ± 3.4, p = 0.668) scores were noted between the two MC phases. Discussion/Conclusion Despite a slightly higher resting ventilation during EF, when both oestrogens and progesterone are at their lowest levels, there were no differences in ventilatory responses to exercise and in AMS between the different phases of the MC. Consequently, there is currently very little evidence to aptly recommend a specific MC phase for mountaineering or any other HA activities (Burtscher et al., 2023). Further investigations are requested to assess whether other physiological responses to HA may be influenced by hormonal variations. References Bärtsch, P., & Swenson, E. R. (2013). Acute high-altitude illnesses. New England Journal of Medicine, 368, 2294-2302. https://doi.org/10.1056/NEJMcp1214870 Burtscher, J., Raberin, A., Brocherie, F., Malatesta, D., Manferdelli, G., Citherlet, T., Krumm, B., Bourdillon, N., Antero, J., Rasica, L., Burtscher, M. & Millet, G. P. (2023). Recommendations for women in mountain sports and hypoxia training/conditioning. Sports Medicine. Advance online publication. https://doi.org/10.1007/s40279-023-01970-6 Goldsmith, E., & Glaister, M. (2020). The effect of the menstrual cycle on running economy. The Journal of Sports Medicine and Physical Fitness, 60(4), 610-617. https://doi.org/10.23736/s0022-4707.20.10229-9 Richalet, J.-P., Larmignat, P., Poitrine, E., Letournel, M., & Canouï-Poitrine, F. (2012). Physiological risk factors for severe high-altitude illness: A prospective cohort study. American Journal of Respiratory and Critical Care Medecine, 185(2), 192-198. https://doi.org/10.1164/rccm.201108-1396OC Saaresranta, T., & Polo, O. (2002). Hormones and breathing. American College of Chest Physicians, 122(6), 2165-2182. https://doi.org/10.1378/chest.122.6.2165